Pragmatic Analysis of the Influence of Local Culture on Students Language Politeness on Social Media - Muhammad Firman Juniansyah; Dedi Sumarna; Siti Tatu Rohbiah (Lex: Journal of Social Sciences and Humanities Perspectives, 2026)
This study aims to analyze the influence of local culture on students’ language politeness on social media from a pragmatic perspective. The research focuses on how students apply politeness strategies in digital communication and how local cultural values shape their language use in online interactions. This study employed a qualitative descriptive method with a pragmatic approach. The participants consisted of junior high school, senior high school, and vocational school students who actively use social media platforms such as WhatsApp, TikTok, Instagram, and Facebook. Data were collected through semi-structured interviews and analyzed using thematic analysis techniques, including data reduction, data display, and conclusion drawing. The findings reveal that local culture strongly influences students’ communication styles, particularly in adapting language based on interlocutors and social contexts. Students tend to use indirect expressions, polite markers such as “please,” “sorry,” and “thank you,” and softened criticism to maintain harmony and avoid conflict. In addition, students frequently utilize emojis, abbreviations, slang, and regional expressions such as “rek” and “euy” to express emotional tone, create solidarity, and reduce misunderstanding in digital interaction. The study also shows that different social media platforms affect the form and level of politeness used by students. WhatsApp encourages more personal and adaptive communication, while TikTok promotes shorter, expressive, and trend-based language. Overall, students’ language politeness reflects the interaction between local cultural norms and modern digital communication practices.